Vagina Monologues' takes on violence against females - Uribes, Tom::::::::: (2013)
The Vagina Monologues' will be presented at 6 p.m. Sunday, April 14, in the Satellite Student Union at Fresno State as part of an international movement to end violence against women and girls.